The dimensions of competency on worker performance mediated by work commitment - Ida Ayu Oka Martini; A. A. N. Eddy Supriyadinata; Ketut Elly Sutrisni; I. Wayan Gde Sarmawa (Cogent Business & Management, 2020)
Weaving workers in Bali are inherited from generation to generation. The ability to weave is obtained without special education/training. The ability to work weaving is obtained independently of the environment. In addition, the difficulty of finding other jobs causes workers to keep working. These two things are important factors in determining the performance of weaving workers in Bali. This study aims to analyze the effect of work competence (knowledge, skills, and attitudes) on employee commitment and performance, the effect of a work commitment on employee performance, and the role of work commitment in mediating the relationship of competence with employee performance. This research was conducted on 168 weaving workers in Bali. Data collection was carried out through distributing questionnaires to research respondents. The data collected was analyzed using the SmartPLS 3.0 program. The results found competencies consisting of knowledge, skills, and attitudes showed a significant positive effect on employee commitment and performance, work commitment also had a significant positive effect on performance. Work commitments also act as mediators of the relationship of competence with employee performance.
Keywords: 650; work competence; skill; knowledge; attitude; work commitment; worker performance